(untitled) (Research, Society and Development, 2024)
Objectives: The present study aims to evaluate microalbuminuria (MAU) in non-diabetic patients with acute coronary syndrome (ACS) admitted to the Hospital Universitário Maria Aparecida Pedrossian, undergoing invasive risk stratification through coronary cineangiocardiography, correlating its dosage with the severity of coronary lesions calculated by the SYNTAX score. Methodology: Observational, prospective study, including non-diabetic patients, over 18 years of age, with ACS, undergoing urine collection for MAU measurement before cardiac catheterization or within 24 hours of hospital admission, during the period from May to December 2023. Patients with a filtration rate below 30 mL/min/1.73 m² and previously undergoing percutaneous coronary intervention or myocardial revascularization were excluded from the study. Results: 20 patients were analyzed, 55% male with a mean age of 61.2 years (± 12.6). Systemic arterial hypertension and dyslipidemia were the most prevalent comorbidities (65%). Acute myocardial infarction (AMI) without ST-segment elevation and AMI with ST-segment elevation were responsible for 80% of patients with ACS. The highest prevalence of coronary vessel involvement was single vessel and triple vessel, each corresponding to 30%, and the average SYNTAX calculated was 12 (± 13.2). The mean MAU value was 197.4 (negative) and the correlation between SYNTAX and MAU rates was not significant (p=0.112; r=-0.377). Conclusion: No statistically relevant relationship was observed between MAU values and the severity of coronary lesions calculated by the SYNTAX score.